Change in marker of hydration correspond to decrement in lower body power following basketball match - Diaz-Castro, F.; Astudillo, S.; Calleja-Gonzalez, J.; Zbinden-Foncea, H.; Ramirez-Campillo, R.; Castro-Sepúlveda, M. (Science & Sports, 2018)
Background: Muscle damage and dehydration are common during basketball matches, but their relationship with performance in this sport is unclear. The aim of this study was to correlate changes in muscle damage (creatine kinase), hydration status (Na+; K+; body mass), and lower body power (countermovement jump) occurring in young athletes during a basketball competition.